PRESSING ISSUES OF PEDIATRIC CONSTIPATION DEVELOPMENT, TREATMENT OPTIONS - M. I. Dubrovskaya; P. V. Parshina ("Paediatrician" Publishers LLC, 2012)
This article covers one of the most pressing issues of pediatric gastroenterology and pediatrics in general - functional constipation.Main pathophysiological mechanisms and etiological factors of constipation development are reviewed in the article adjusted for age and a period of child development. It also includes modern constipation classifications and therapeutic options in pediatric patients, developed in NASPGHAN including education of patients and their parents such as behavioral treatment.